Mandates and funding the divorce of implementation from policy - Joaquin, Maria Ernita T. (2001)
We remain students of public policy because we are aware that policy design is of utmost consequence to both the integrity of the implementation process as well as the achievability of program objectives, two items that could very well make up the definition of good governance. For even if consensus is gained in the shaping-which is near to impossible - a policy that is wanting in terms of implementation may be more insidious to the field of public policy and intergovernmental relations than adopting no policy at all. This article argues that creating national programs without adequate provision for their total implementation is a disservice to the implementing institutions directly, and the nation ultimately. If no one took an inventory, we are merely accumulating unimplemented and unimplementable laws, while wondering where the problem of governance lies. A practical way of looking at policy has never been more urgent.
Keywords: Public policy (Law); Government policy